The implementation of gamification with video media variations to improve students’ concept mastery in science learning - Oskar Erens Tumewu; Saprudin Saprudin; Usman Sambiri; Rahim Achmad; Mardia Hi Rahman; Fatma Hamid (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examines the effectiveness of ICT-based gamification combined with different video presentation types in improving students’ concept mastery of earthquakes and disaster mitigation. A quasi-experimental design was employed involving 50 eighth-grade students from a junior high school in West Halmahera Regency, North Maluku, who were divided into three groups: gamification with dialogue video, gamification with monologue video, and conventional learning. Students’ concept mastery was measured using a validated 25-item multiple-choice test administered before and after instruction. Data were analyzed using normalized gain scores and inferential statistics. The results indicate that students who learned through gamification supported by video media showed significantly higher concept mastery compared to those in conventional learning. Although the dialogue video group demonstrated higher gains than the monologue video group, the difference was not statistically significant. These findings suggest that gamification supported by video media is an effective instructional strategy, while highlighting the importance of interactivity in video design to support meaningful concept learning in science education.